Phenomenon of Demikhov. At N.V. Sklifosovsky Institute (1960–1986). V.P. Demikhov and his experiments in the field of organ transplantation in 1968–1973 - S. P. Glyantsev (Трансплантология (Москва), 2023)
The article analyzes the experimental studies of V.P. Demikhov conducted by him in 1968-1973, by studying the content of his report on the work done during this period of time and presented at the Meeting of the Academic Council of N.V. Sklifosovsky Institute in July 1973 for the re-election for the position of the Head of the Organ Transplantation Laboratory for a new 5-year term. It follows from the analyzed document that the extent of the research made by V.P. Demikhov and his staff significantly exceeded the data that were presented in the Institute's reporting documents for 1973, in the Research Plans for 1974, and the plans for implementing the research results in healthcare practice in 1974. The Table that illustrated the report indicated that in 1968–1973 V.P. Demikhov conducted more than 485 different experiments, including transplantation of vital organs, experiments on perfusion of isolated organs, resuscitation of cadaveric hearts, and heterogeneous blood transfusion. He actively collaborated with surgeons from many clinical institutions in Moscow (Institute of Tuberculosis, S.P. Botkin Hospital, Hospitals of the Moscow Military District) and other cities of the country (Frunze, Tyumen), conducting joint experimental and clinical studies with them. However, attempts to introduce the methods developed by him into clinical practice were futile. Of all his achievements in different years, the method of upper limb reimplantation was successfully applied in clinic in 1971 by Professor B.D. Komarov.